Paper & Place: The Poetry of Billy Mills. Issue 1 (May 2016) - Davis, Alex
Abstract : This essay discusses the issue of place and its representation in the work of the contemporary Irish experimental poet, Billy Mills. It considers the ontological priority Mills's poetry and related critical work grant the object world, and the necessarily provisional quality of the 'mapping' of the environment in verbal art. Mills's ecopoetics are contrasted with the pastoral poetic tradition, as he construes it, with the poetry of Seamus Heaney, and with Language Writing. In conclusion, Mills's practice as a translator is shown to display an attentiveness to nonlinear form that, as a critic, he identifies in the work of contemporaries including Maurice Scully, Geoffrey Squires, and Catherine Walsh.